2022
DOI: 10.1002/rmv.2390
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of novel serum biomarkers, including C‐reactive protein to albumin ratio and fibrinogen to albumin ratio, in COVID‐19 disease: A meta‐analysis

Abstract: With COVID‐19 still hovering around and threatening the lives of many at‐risk patients, an effective, quick, and inexpensive prognostic method is required. Few studies have shown fibrinogen to albumin ratio (FAR) and C‐reactive protein to albumin ratio (CAR) to be promising as prognostic markers for COVID‐19 disease. However, their implications remain unclear. This meta‐analysis aimed to elucidate the prognostic role of FAR and CAR in COVID‐19 disease. A systematic literature search was undertaken using PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“… 30 At the same time, it could bind and inactivate many inflammatory promoters, such as pathogen-related molecular patterns, bioactive lipid metabolites, reactive oxygen species, and nitric oxide. A recent meta-analysis 31 also further confirmed that CAR was a good predictor of mortality risk in patients with COVID-19. The good adaptability of CAR to changes in these two diseases may explain its best performance in the present study.…”
Section: Discussionmentioning
confidence: 81%
“… 30 At the same time, it could bind and inactivate many inflammatory promoters, such as pathogen-related molecular patterns, bioactive lipid metabolites, reactive oxygen species, and nitric oxide. A recent meta-analysis 31 also further confirmed that CAR was a good predictor of mortality risk in patients with COVID-19. The good adaptability of CAR to changes in these two diseases may explain its best performance in the present study.…”
Section: Discussionmentioning
confidence: 81%
“…To date, previous studies have indicated that FAR could be an independent predictor of worse outcomes in different disease processes. 6 , 35 However, only a few studies have reported the association of high FAR levels with poor outcomes after ischemic stroke. For example, it has been reported that a high FAR predicts poor functional outcome in patients with acute pontine infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Pro-inflammatory cytokines such as TNF-α and IL-6 inhibit the production of ALB. The metaanalysis also showed that elevated CRP levels and decreased ALB levels were the most common laboratory findings in patients with COVID-19 (35). Experiments show that ALB causes the upregulation of ACE and the downregulation of ACE2 by interrupting the balance of ACE and ACE2 (36).…”
Section: Data Availability Statementmentioning
confidence: 94%